Integrating Sensor Technologies with Conversational AI: Enhancing Context-Sensitive Interaction Through Real-Time Data Fusion - Joseph C. Kush (Sensors)
This article examines how sensor technologies (such as environmental sensors, biometric sensors, and IoT devices) intersect with conversational AI models like ChatGPT 4.0. In particular, this article explores how data from different sensors in real time can improve AI models’ comprehension of surroundings, user contexts, and physical conditions. Lastly, this article delves into the scientific principles supporting sensor technologies, data processing methods, and their fusion with generative models such as ChatGPT to develop adaptable, dynamic systems that engage with humans intelligently in real time. Some of the specific topics that are investigated include the science behind sensor networks and acquiring real-time data, how ChatGPT can analyze sensor data to generate dialogue that is sensitive to context, instances in healthcare (such as using wearable sensors along with AI chatbots for patient treatment), and smart homes (interaction with AI assistants driven by sensors). These subjects will prove advantageous for researchers in sensor technology as well as AI development, showcasing interdisciplinary progress in smart systems.